Medical Writing for Continuing Education in the Health Professions: A Competency Model - Haifa Kassis; Donald Harting (Taylor & Francis Group, 2024)
Medical writers assist continuing medical education (CME)/continuing professional development (CPD) providers in planning and delivering educational programmes. Their responsibilities include developing needs assessments and instructional content for accredited CME-CPD. However, to the best of our knowledge, a competency model for training writers who develop CME-CPD materials does not exist. We used a modified Delphi method to identify knowledge areas, skills, attitudes, and deliverables (KSADs) to include in a model for training the next generation of CME writers. Over 3 rounds of questionnaires, we asked a diverse panel of stakeholders to rate an initial set of KSADs, suggest additional KSADs, and provide rationales for their ratings. Panellists rated each KSAD from 1 (strongly disagree) to 5 (strongly agree) based on whether it should be included in the model. Panellists received anonymised reports of results between rounds and could change their previous ratings. Of 22 panellists who agreed to participate, 20 (90.9%) completed all 3 rounds. Of 83 suggested KSADs, 44 (53%) received a final average rating of at least 4, meeting predefined criteria for consensus. In total, we identified 38 KSAs necessary for CME writers to excel. These KSAs cover a wide range of topics from various fields, including accredited continuing education, medicine and healthcare, and medical writing and communications. We also identified 6 in-demand deliverables, including needs assessments, outcomes questions, slide decks, interactive patient case studies, agendas for proposed educational programmes, and scripts for video or audio recordings. This new competency model may help guide the development of training programmes for medical writers specialising in CME-CPD.